Urgensi Penerapan Audit Syariah untuk Meningkatkan Transparansi dan Akuntabilitas Laporan Keuangan Lembaga Keuangan Syariah - Syahdina, Nurul Aghnia; Fera, Fetti; Adawiyah, Radyatul; Masyhuri, Masyhuri (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Sharia audit is an important supervisory tool used to ensure that Islamic Financial Institutions (IFI) comply with sharia principles, while also serving as the main foundation in creating transparency and accountability in financial statements. This study aims to explore the importance of implementing sharia audit in Islamic financial institutions in improving the quality of transparency and accountability of financial statements. The method used is a literature review with a descriptive qualitative approach. The results show that sharia audit conducted comprehensively by the Sharia Supervisory Board (SSB) is able to detect deviations from sharia principles, increase the confidence of interested parties, and strengthen the management of Islamic financial institutions. The main challenges found include the limited auditors who have dual abilities in accounting and fiqh muamalah, misalignment of sharia audit standards, and lack of transparency in reporting audit results to the public. This study suggests the enforcement of sharia audit regulations, increasing human resource capacity, and the use of information technology to support transparency in Islamic financial reporting.